Measuring the effect of adaptive directionality and split processing on noise acceptance at multiple input levels. - Kuk, Francis; Slugocki, Christopher; Davis-Ruperto, Neal; Korhonen, Petri (International Journal of Audiology, 2023)
This study used the multi-level Tracking of Noise Tolerance (TNT) test to compare Augmented Focus (AF) or split processing over non-AF processing with adaptive directionality (non-AF-dirm) and with an omnidirectional microphone (non-AF-omni). This was a single-blind, within-subject repeated measures design. Nineteen listeners with a mild-to-moderate hearing loss. The listeners' task was to determine their tolerable noise level (TNL) in the sound-field at four fixed speech levels (i.e. 62, 68, 75, and 85 dB SPL) in the unaided condition and the different aided conditions. The speech passages were presented from 0° while a continuous speech-shaped noise was presented from 180°. Each condition was tested twice, each in a different counterbalanced order. AF improved TNL by an average of 2.9 dB over non-AF-dirm. Adaptive directionality improved the aided TNL by 4.7 dB over the non-AF-omni condition. The unaided TNL was similar to the aided non-AF-omni TNL. Whereas a stable TNL was reached in 20–30 s for non-AF-dirm, it took AF < 15 s to reach a stable TNL at all input levels. This study shows that AF allowed 2.9 dB of signal-to-noise ratio (SNR) improvement over that of non-AF-dirm and 7.6 dB over the aided non-AF-omni condition.